2020
DOI: 10.1038/s41598-020-59411-7
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin liposomes ameliorate streptozotocin-induced diabetic nephropathy in diabetic rats

Abstract: The effects of quercetin liposomes (Q-PEGL) on streptozotocin (STZ)-induced diabetic nephropathy (DN) was investigated in rats. Male Sprague Dawley rats were used to establish a STZ induced DN model. DN rats randomly received one of the following treatments for 8 weeks: blank treatment (DN), free quercetin (Que), pegylated liposomes (PEGL) and pegylated quercetin liposomes (Q-PEGL). A group of healthy rats served as the normal control. The fasting blood glucose (FBG), body weights (BWs), renal hypertrophy inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…Quercetin, a natural flavonoid, is well known to possess multiple pharmacological functions, including but not limited to antioxidant, anti-inflammatory, anticancer, antidiabetic, neuroprotective, and antiobesity [ 51 , 52 ]. The use of quercetin contributes to a meaningful improvement in disease symptoms, renal hypertrophy index, renal histopathology, oxidative stress, and blood glucose in a rat model of DN [ 41 ]. Furthermore, quercetin treatment is beneficial to antioxidant capacity and vasoprotective effects against STZ-induced ER stress of diabetic rats via reducing the lipid peroxidation and increasing the expression of vascular endothelial growth factor (VEGF) and its receptor, VEGFR2, and nitric oxide (NO) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin, a natural flavonoid, is well known to possess multiple pharmacological functions, including but not limited to antioxidant, anti-inflammatory, anticancer, antidiabetic, neuroprotective, and antiobesity [ 51 , 52 ]. The use of quercetin contributes to a meaningful improvement in disease symptoms, renal hypertrophy index, renal histopathology, oxidative stress, and blood glucose in a rat model of DN [ 41 ]. Furthermore, quercetin treatment is beneficial to antioxidant capacity and vasoprotective effects against STZ-induced ER stress of diabetic rats via reducing the lipid peroxidation and increasing the expression of vascular endothelial growth factor (VEGF) and its receptor, VEGFR2, and nitric oxide (NO) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking, a method of analyzing the binding site and affinity between the conformation of molecules and macromolecular targets, has been considered a crucial technique for structure-based drug discovery [ 40 ]. The core DN-related genes targeted by the AR-PN herb pair bioactive components was identified according to the component-target-pathway network, which were further validated by molecular docking with the experimentally verified AR-PN herb pair bioactive components possessing renoprotective effects on DN, including quercetin [ 41 ], kaempferol [ 42 ], formononetin [ 43 ], and isorhamnetin [ 44 ]. First, the mol2 formats of these bioactive components were obtained from the TCMSP database and PubChem database, which were converted to the format of pdb and pdbqt via Pymol software and AutoDock Tools 1.5.6, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, 3 of them had been proven to have kidney protection effect by experiments. For example, quercetin liposomes had renal protective effects of reducing oxidative stress, attenuating AGE expression, and delaying the progression of DKD [26]. Luteolin attenuated DKD mainly via suppression of inflammatory response and oxidative response [27].…”
Section: Discussionmentioning
confidence: 99%
“…It also has anti-oxidant, hypoglycemic, hypolipidemic, tumor suppression, and anti-in ammatory effects [28.29.30]. One study showed that quercetin liposome or free quercetin can prevent weight loss, decrease kidney hypertrophy index, decrease blood glucose level and 24-hour urine protein in diabetic nephropathy model rat [31]. Kaempferol is a kind of natural peroxisome proliferator-activated receptor-γ(PPARγ) agonist, and PPARγ agonist has also become a common drug in the treatment of diabetes and its complications [32].…”
Section: Discussionmentioning
confidence: 99%